Manager`s competence model in the face of new economic challenges - research report - Igielski, Michał (Zielona Góra: Faculty of Economics and Management Press)
The main aim of the article is to try to determine, on the basis of the conducted research, the optimal competencies and skills that a manager should have in order to effectively manage the team (in the opinion of its members). The author will also indicate the connection and differences between the obtained data resulting from the Polish reality and the contemporary guidelines for the IPMA competence model. Apart from literature analysis, the author chose a diagnostic survey (research technique - questionnaire) as another research method.
Keywords: industrial revolution; competences; managerial competence; rewolucja przemysłowa; kompetencje; kompetencje kierownicze